In the presence of gods and spirits: Hirata Atsutane and his collaborators - Walthall, Anne (Michigan monograph series in Japanese studies, 2025)
"In the Presence of Gods and Spirits brings to life the early nineteenth century Japanese religious leader and scholar Hirata Atsutane, whose fear of Russian incursion onto Japan's soil led him to redefine what it means to be Japanese. Atsutane advocated the study of the Way of the Gods, commonly known as Shinto, to explain what happens to the soul after death and to cultivate a Japanese identity centered on gods, spirits, and the emperor. His teachings would later attract thousands of followers and feed the movements that led to the Meiji Restoration. Drawing on the concept of material religion, Walthall demonstrates how Atsutane and his collaborators sought out knowledge of the unseen world and educated others, while seeking to bring themselves closer to the gods and spirits. This work showcases Atsutane and his community's legacy, which has had a profound influence on Japanese society, religious belief, and culture far beyond his lifetime"-- Provided by publisher